Pengaruh Kemudahan Penggunaan dan Persepsi Harga Terhadap Keputusan Pembelian di TikTok Shop - Riris Ode Antea; Asri Jaya; Nurlina Nurlina (CV. Aksara Global Akademia, 2026)
This research is motivated by the increasing use of TikTok Shop as a social commerce platform that makes it easier for consumers to make purchases through interactive features and various price promotion strategies. This study aims to analyze the influence of ease of use and price perception on purchase decisions on TikTok Shop. The population in this study is students of the Management Study Program of the University of Muhammadiyah Makassar class of 2022–2025, with a sample of 95 respondents determined using the Slovin technique. The analysis method used is multiple linear regression supported by validity, reliability, and classical assumption tests. The results of the study show that ease of use and partial price perception have a positive and significant influence on purchase decisions on TikTok Shop. High ease of use can increase consumer convenience in transactions, while good price perception encourages consumers to make purchase decisions. The implications of this study show the importance of improving the quality of the system and pricing strategies in supporting consumer purchase decisions on social commerce platforms